Kebijakan Pesantren dalam Menjaga Tradisi dan Modernisasi - Risalotus Sofwah; Moh. Yusup Saepuloh Jamal; Try Riduwan Santoso (Prodi PAI IAILM Suryalaya, 2024)
This study aims to explore the implementation of educational policies at Pondok Pesantren Al-I'ttihad Pagerageung, Tasikmalaya, which seeks to balance the preservation of traditional Islamic education with the demands of modernization. Initially known for its traditional teaching methods such as sorogan and bandongan, Pesantren Al-I'ttihad has innovated by adopting a formal curriculum, utilizing information technology, and providing modern educational facilities. Additionally, the pesantren has introduced practical skill training, such as entrepreneurship and agriculture, to equip students with relevant expertise for the contemporary era. This research employs a descriptive qualitative approach through field studies, involving in-depth interviews, observation, and documentation. The findings indicate that the modernization of education in this pesantren is a response to social change without losing the essence of Islamic tradition. The central role of the kyai as a leader in educational policymaking is crucial in bridging the traditional pesantren system with modern societal needs. Pesantren Al-I'ttihad has successfully maintained its contribution to the moral and intellectual development of the nation through a combination of tradition and innovation.